Fungos conidiais sapróbios da Amazônia no controle de Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) - Rizzi, Thiago de Souza (2020)
Spodoptera frugiperda is a polyphagous insect of great economic importance for agriculture due to the damage caused in several cultures in the world. Currently, the difficulties faced are in the control of this pest, in view of the selection of resistant for the most used control technologies, the chemical control and the cultures that express the base proteins of Bacillus thuringiensis. In this way, the prospect of new control strategies is desired. In this scenario, the biological control of insects stands out with the use of microorganisms. Fungi correspond to most of the microorganisms used in the biological control of insects. Conidial saprobic fungi have interesting characteristics for their use in biological control, however research with these microorganisms is uncommon, and mainly at taxonomic level. The Amazon region has a great biodiversity, being an important tool for the development of technologies for the various sectors of human life, as well as for the biological control of insects. Conidial saprobic fungi have shown interesting results in the biological control of phytopathogens, since they produce several compounds in their secondary metabolism, these compounds have low molecular mass and can belong to different chemical classes. Although these compounds may have an insecticidal action, there are few studies evaluating these fungi in the control of insects, mainly lepidopterans. The objective of this study was to evaluate the control of S. frugiperda by means of filtrates, at a concentration of 20%, of saprobic conidial fungi from the Amazon. Two bioassays were carried out evaluating the different modes of action, one of ingestion and one of contact for the fungal filtrates of Brachysporiella sp.; Gonytrichum sp.; Ellisembia sp. and Pseudobotrytis terrestris, in addition to two controls, sterile water and Pirate® (chlorfenapyr) under laboratory conditions. The insecticidal action by filtrates of saprobic conidial fungi on S. frugiperda did not show significant effects regardless of the form of use, be it contact or ingestion, with a maximum larval mortality of 56.6%, but without differentiation from the control. Gonytrichum sp. showed higher weights of larva and pupa, and a smaller larval cycle in the application by ingestion. Although the insecticidal action was reduced, there was an ability to alter the biology of the species, reducing the weight of the larva, pupa and life cycle of S. frugiperda, mainly due to the action of Pseudobotrytis terrestris filtrate.